Repeated influenza vaccination and hospitalization outcomes among older patients with cardiovascular or respiratory diseases. Issue 12 (2nd December 2021) - Pang, Yuanjie; Yu, Mengke; Lv, Min; Lu, Ming; Wu, Jiang; Xie, Zheng; Huang, Yangmu
ABSTRACT: Influenza vaccination in a single season protects against hospitalization outcomes among older adults hospitalized for cardiovascular or respiratory diseases, but the effectiveness of repeated influenza vaccination is less clear. Four hospitalization outcomes (in-hospital death, re-admission, length of stay, and direct medical costs) were extracted from the Beijing Urban Employee Basic Medical Insurance database in 2015–2016 for adults aged ≥60 years hospitalized for cardiovascular or respiratory diseases. Vaccination status during three influenza seasons (2013/2014-2015/2016) was ascertained through linkages to the Beijing Elderly Influenza Vaccination database. The summer months (June–August) were used as a reference period to control unmeasured confounders during the influenza season. There were 99, 135 periods of observation in the analysis, with 8.3% participants receiving influenza vaccination in all three seasons. After adjusting for confounders, influenza vaccination in all three seasons was associated with a lower risk of re-admission among patients with cardiovascular diseases (odds ratio 0.71 [95% CI 0.53–0.96]) and a lower risk of death among patients with respiratory diseases (0.68 [0.46–0.98]) compared with those unvaccinated in any season. Among patients with cardiovascular diseases, influenza vaccination in all three seasons was also associated with a non-significant lower risk of death (0.66 [0.44–1.03]) in addition to shorter hospital stays and lower direct medical costs. When stratified by history of vaccination, the effectiveness of current season vaccination was similar among patients with cardiovascular or respiratory diseases ( p -value for heterogeneity all >0.05). Repeated influenza vaccination protected against hospitalization outcomes among older adults with cardiovascular or respiratory diseases. Plain language summary: We found that influenza vaccination in three seasons (2013–2016) was associated with lower risk of in-hospital death and re-admission among older adults hospitalized for cardiovascular disease and with lower risk of in-hospital death among those hospitalized for respiratory disease. In addition to the effectiveness of influenza vaccination on preventing influenza itself, this study suggested that there were protective effects of repeated influenza vaccination on cardiovascular or respiratory diseases.